Low-temperature synthesis of a graphene-based, corrosion-inhibiting coating on an industrial grade alloy. (15th May 2019) - Halkjær, Susanne; Iversen, Jon; Kyhl, Line; Chevallier, Jacques; Andreatta, Federico; Yu, Feng; Stoot, Adam; Camilli, Luca; Bøggild, Peter; Hornekær, Liv; Cassidy, Andrew M.
Highlights: Prepare a 7 nm thick graphene based coating on an Inconel 625 substrate. A low temperature, molecular polymerisation recipe prevents substrate degradation. Coating reduces corrosion current by two orders of magnitude in acidic conditions. Abstract: The use of graphene materials as protective coatings for metallic substrates has received much attention because of graphene's ability to seal a metal and prevent the diffusion of most corrosive species to the metal surface. The application of graphene-based coating technology to industrially relevant samples, however, is hindered by the high growth temperatures required to prepare functional and efficient protective graphene layers. The growth temperatures typical for popular catalysts and precursors are incompatible with most relevant alloys. Here, we present a low-temperature synthesis route to a graphene-based coating, using a complex metallic alloy, Inconel 625, as an example substrate. We demonstrate that the coating reduces the sample corrosion current by two orders of magnitude and also shifts the open circuit potential from −308 mV to + 129 mV. We present an extensive characterisation of the coating and the coating synthesis procedure. The procedure relies on a surface-activated, thermally-induced polymerisation reaction and the method should be transferable to other metallic alloys.